2021
DOI: 10.3390/buildings11120572
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Learning Styles on Perception and Preference of Learning Spaces in the University Campus

Abstract: Good academic performance will occur when learning spaces match or support individual preference and needs. This effect depends on environmental characteristics and individual attributes. Learning styles (LSs) have been used as a tool to capture the behavioral and psychological characteristics of learners in the process of learning activities, which provide instructions to address their learning needs. However, few have focused on the perceptual characteristics of learning space from the view of distinct learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…In the learning process, empirically, perception has a significant influence, both in terms of learning preparation, the process, and the evaluation of the learning itself. The research results of Wang & Han [24] Suryanti et al [25] stated that students' positive perceptions play a role in learning styles and can increase their motivation and learning outcomes. The results of this research align with research [26] that shows that students who have positive perceptions of subjects tend to have better learning outcomes than students who have negative perceptions.…”
Section: Sincementioning
confidence: 99%
“…In the learning process, empirically, perception has a significant influence, both in terms of learning preparation, the process, and the evaluation of the learning itself. The research results of Wang & Han [24] Suryanti et al [25] stated that students' positive perceptions play a role in learning styles and can increase their motivation and learning outcomes. The results of this research align with research [26] that shows that students who have positive perceptions of subjects tend to have better learning outcomes than students who have negative perceptions.…”
Section: Sincementioning
confidence: 99%
“…It is observed that America is the most outstanding and Asia has had little contribution. The problem under study has been identified in the formation of learning teams, with the aim of establishing mixed learning styles as a strategy for the formation of efficient and effective teams [6]- [8]. For which, the qualitative approach with non-experimental design was considered; having carried out a pre-test and a post-test for conceptual understanding.…”
Section: Specific Formmentioning
confidence: 99%
“…Previous research has found that students generally conduct their study-related activities at home or in an educational building [4], and spend substantial time inside these places [5]. Therefore, understanding students' preferences of these places can help to provide indoor environments that support their academic performance and well-being [6,7]. These preferences can be related to indoor environmental aspects and psychosocial aspects [8].…”
Section: Introductionmentioning
confidence: 99%